The moon within - Salazar, Aida (Arthur A. Levine Books, 2019)
Describes in verse how eleven-year-old Celi Rivera is anxious about her approaching period because her mother wants to hold a traditional Mexican moon ceremony to celebrate the occasion. Meanwhile, Celi's best friend explores what it means to be gender fluid, and Celi explores her feelings for a boy. However, when the boy she has a crush on makes mean comments about her best friend, Celi must make a decision.